DUHOK RIVER BASIN GEOMORPHOMETRIC AND ITS ROLE IN SUSTAINABLE DEVELOPMENT - S. M, DR. NISHAN (Journal of Duhok University, 2019)
The Duhok river basin is located in its total area (399km 2) within the boundaries of limits to district of Duhok .one of the district of the province of Dohuk map NO/1/ The areas is geographically determined by mountain Zawa the sorth and Khabur basin the north and mountain bekher the west and khosar basin of the east and between the width circle (36-50-and 37-0-) longitude(42-50-and 43-10-) of the east. The objectives of the research is to study the geomorphometric characteristics of the area and the extent to which they can be utilized in different development field and sustainability. The research section is divided into third axes;The first of which is the study of the environmental characteristics of the area, The research contained in the second axis morphometric characteristics, While the last research concerned studying the problems and aspects of sustainable development through the investment of the possibilities of the ground area